Investigating a potential association between agenesis of the third molars and variations in dental crown dimensions - Gloria Guht; Christian Kirschneck; Nikolaos Daratsianos; Cristiano Miranda de Araujo; Natanael Henrique Ribeiro Mattos; Flares Baratto-Filho; Peter Proff; Diulia Pereira Bubna; Svenja Beisel-Memmert; Erika Calvano Küchler (PLoS ONE, 2026)
The aim of this study was to investigate the association between third molar agenesis and mesiodistal crown dimensions in individuals from Germany. The sample consisted of 314 (156 males and 158 females) orthodontic patients, divided into two groups: one group with individuals presenting at least one congenitally missing third molar and a control group with individuals having a full complement of 32 teeth. The mesiodistal crown width of each fully erupted permanent tooth was measured at its maximum dimension. The t-test was used to compare mesiodistal width between groups, with additional analyses according to gender and dental arch. A chi-square test evaluated the distribution of third molar agenesis among genders, and odds ratios (OR) with 95% confidence intervals (CI95%) were calculated. Pearson correlation assessed the relationship between the number of missing third molars and mesiodistal crown size. A total of 89 patients with third molar agenesis and 225 controls were included. Forty-three males and 46 females presented agenesis; with no significant association between gender and third molar agenesis (p = 0.760; OR = 1.08; 95% CI = 0.66–1.73). Mesiodistal dimensions were significantly different between males and females (p < 0.05). Patients with third molar agenesis exhibited a significant reduction (p < 0.05) in mesiodistal size across all teeth, most notably in second molars and maxillary lateral incisors. In males, all teeth in the agenesis group showed smaller dimensions compared to controls, with differences ranging from −0.43 to −0.15, the largest observed in the second maxillary molars (−0.43). In females, 18 of 28 teeth showed significant reductions, ranging from −0.42 to 0.00, with the largest difference in the left second mandibular molar (−0.42). The correlation between the number of missing third molar and mesiodistal size showed some negative moderate correlations, especially for lower canines (left r = −0.459, and right r = −0.534). In conclusion, third molar agenesis is associated with reduced mesiodistal crown dimensions in individuals from Germany, with this effect being more pronounced in males than in females.